Continuous and dually continuous idempotent L-semimodules - O. R. Nykyforchyn (Математичні Студії)
We introduce L-idempotent analogues of topological vector spaces by means of domain theory, study their basic properties, and prove the existence of free (dually) continuous L-semi- modules over domains, (dually) continuous lattices and semilattices.